IODINE DISTRIBUTION IN SOME NIGERIAN FISHES: Short Communication - Asaolu, S S; Asaou, M F (Biological Sciences - PJSIR, 2002)
Iodine was found present in tested organs of the selected fish. The flesh of Sadinella auritea (Fl) has the highest iodine content with an average value of 103.42 mg g-1 while the tissue of Ethamalosa fimbriala (F5) has the least with an average of 20.21 mg g-1 dry weight. The iodine distribu tion number (IDN) and coefficient of variation indicate a wide variation of iodine from one organ to another. The result obtained shows that Nigeria fishes contains sufficient iodine for dietary intake